2020
DOI: 10.1111/jfs.12792
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating food safety and hygiene knowledge and practices among foodservice staff of feeding scheme in the primary schools in Soweto, South Africa

Abstract: The study was to evaluate the food safety knowledge and hygiene practices among food handlers. A total of 42 food handlers in 13 basic schools under the School Feeding Scheme, Soweto, South Africa were recruited for the study using purposive and convenience sampling methods for the respondents and institutions, respectively. A piloted self‐administered questionnaire was used. All the respondents were female (100%) with the majority being between the ages of 31 and 40 (40%) and had secondary education (63%). Ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 42 publications
(51 reference statements)
2
10
0
Order By: Relevance
“…Food intoxication often begins with diarrheal diseases, then progresses to other serious diseases such as kidney and liver failure, brain and neural disorders, reactive arthritis, cancer, and eventually death (WHO/Yoshi Shimizu, 2022 ). The inability of the food workers to conform to food safety and hygiene standards during food preparations has been reported in Ghana (Parry‐Hanson et al, 2016 ), Brazil (Cortese et al, 2016 ), Saudi Arabia (Ayaz et al, 2018 ), and South Africa (Mgqibandaba et al, 2020 ). It is therefore incumbent on the food handlers, most importantly the institutional caterers, to have at least certain skills and knowledge to implement food safety and personal hygiene standards to reduce, if not prevent, the high rate of foodborne infections.…”
Section: Introductionmentioning
confidence: 99%
“…Food intoxication often begins with diarrheal diseases, then progresses to other serious diseases such as kidney and liver failure, brain and neural disorders, reactive arthritis, cancer, and eventually death (WHO/Yoshi Shimizu, 2022 ). The inability of the food workers to conform to food safety and hygiene standards during food preparations has been reported in Ghana (Parry‐Hanson et al, 2016 ), Brazil (Cortese et al, 2016 ), Saudi Arabia (Ayaz et al, 2018 ), and South Africa (Mgqibandaba et al, 2020 ). It is therefore incumbent on the food handlers, most importantly the institutional caterers, to have at least certain skills and knowledge to implement food safety and personal hygiene standards to reduce, if not prevent, the high rate of foodborne infections.…”
Section: Introductionmentioning
confidence: 99%
“…Computation was used to obtain the predators and the significant association (P ≤ 0.05) among some demographic characteristics, and experience and average production capacity were investigated using Spearman's rho correlation coefficient. Preliminary analyses were performed to ensure no violation of the assumptions of normality, linearity, and homoscedasticity [8].…”
Section: Discussionmentioning
confidence: 99%
“…It is important that school foodservice director recognize the added complexity of the NSLP guidelines and therefore the increased pressure put on school foodservice workers. Mgqibandaba et al (2020) found that food handlers in schools who are responsible for food handling need to get trainings and workshops to maintain acceptable food safety and hygiene standards. Further stating that improper handling of foods is responsible for most cases of foodborne illness and training for caterers has proven to improve food hygiene knowledge and awareness.…”
Section: Discussionmentioning
confidence: 99%
“…showed that participants in positions of authority had significantly greater score increases in the confidence construct. This shows the importance of training on content that is immediately relevant to participants daily work and showing how they can apply the training content in their "real-world" jobs.It is important that school foodservice director recognize the added complexity of the NSLP guidelines and therefore the increased pressure put on school foodservice workers Mgqibandaba et al (2020). found that food handlers in schools who are responsible for food handling need to get trainings and workshops to maintain acceptable food safety and hygiene standards.…”
mentioning
confidence: 99%